Brain drain and economic growth: Evidence of productivity growth from brain circulation - Woosik Yu (European Journal of Government and Economics (EJGE), 2021)
This paper analyzes the effect of the so-called 'brain drain' on economic growth through the channel of growth in total factor productivity. We analyze panel data that measure the severity of brain drain, which are from IMD and the U.S. National Science Foundation. Our analysis shows that middle-income countries have more brain drain compared to the group of high-income countries. Also, emerging economies that grow fast tend to experience more brain drain. Our results from fixed effects regression models show that that brain drain has a significant and positive impact on economic growth, and the main channel is productivity growth. This can be considered as evidence of the positive effects of 'brain circulation', which is one of the brain drain phenomena that settlement of the talents in advanced countries can eventually help improve the productivity of home country by the sharing of advanced technologies and skills around them with colleagues in motherland. Therefore, a strategy of utilizing overseas resident talents should also be considered, alongside the brain-attraction policy.
Keywords: O11; O15; O47; F43; 330; brain drain; brain circulation; economic growth; total factor productivity